Предмет: Математика, автор: olenka3123

решительно пож срочно надо очень

Приложения:

Ответы

Автор ответа: julyap
0
 frac{b+4}{b^2+16}  *( frac{b+4}{b-4} + frac{b-4}{b+4} )= frac{2}{b-4}  \  \ 1)  frac{b+4}{b-4} + frac{b-4}{b+4} = frac{(b+4)(b+4)+(b-4)(b-4)}{(b+4)(b-4)} =  frac{(b+4)^2+(b-4)^2}{(b+4)(b-4)} = \  \ = frac{b^2+16+8b+b^2+16-8b}{(b-4)(b+4)} = frac{2b^2+32}{(b-4)(b+4)}  \  \ 2)  frac{b+4}{b^2+16} * frac{2(b^2+16)}{(b-4)(b+4)} = frac{2}{b-4}  \  \  \   frac{2}{3.75-4} = frac{2}{-0.25} =-8
Похожие вопросы
Предмет: История, автор: ж88